(untitled) (Revista Brasileira de Contabilidade e Gestão, 2021)
Credit cooperatives seek to adapt to new market needs in order to deliver solutions to their associates through the use of smartphone technologies, known as mobile banking. This study aims to investigate the contribution of incremental innovation to mobile banking services in a credit cooperative in the city of Guanhães-MG. Regarding the methodology, the research refers to an applied, qualitative and descriptive study. Data for the preparation of the article were collected through the cooperative’s website and social medias and others made available by the cooperative’s executive board. After surveying and interpreting the collected data, it should be noted that incremental innovation for mobile banking is a topic of great importance so that credit unions do not lose competitive advantage over competitors. Through this type of innovation, cooperatives can deliver more value and exceed the expectations of their associates, also contributing to the promotion of the regional economy. The incremental innovation implemented at the institution was of paramount importance for maintaining banking services and achieving positive results.